Oral glucose tolerance test is needed for appropriate classification of glucose regulation in patients with coronary artery disease: a report from the Euro Heart Survey on Diabetes and the Heart. Issue 1 (11th August 2006) - Bartnik, M; Rydén, L; Malmberg, K; Öhrvik, J; Pyörälä, K; Standl, E; Ferrari, R; Simoons, M; Soler-Soler, J
Abstract : Background: Patients with coronary artery disease (CAD) and abnormal glucose regulation (AGR) are at high risk for subsequent cardiovascular events, underlining the importance of accurate glucometabolic assessment in clinical practice. Objective: To investigate different methods to identify glucose disturbances among patients with acute and stable coronary heart disease. Methods: Consecutive patients referred to cardiologists were prospectively enrolled at 110 centres in 25 countries (n = 4961). Fasting plasma glucose (FPG) and glycaemia 2 h after a 75-g glucose load were requested in patients without known glucose abnormalities (n = 3362). Glucose metabolism was classified according to the World Health Organization and American Diabetes Association (ADA; 1997, 2004) criteria as normal, impaired fasting glucose (IFG), impaired glucose tolerance (IGT) or diabetes. Results: Data on FPG and 2-h post-load glycaemia were available for 1867 patients, of whom 870 (47%) had normal glucose regulation, 87 (5%) had IFG, 591 (32%) had IGT and 319 (17%) had diabetes. If classification had been based on the ADA criterion from 1997, the proportion of misclassified (underdiagnosed) patients would have been 39%. The ADA 2004 criterion would have overdiagnosed 8% and underdiagnosed 33% of the patients, resulting in a total misclassification rate of 41%. For ethical concerns and practical reasons, oral glucose tolerance test (OGTT) was not conducted in 1495 of eligible patients. These patients were more often women, had higher age and waist circumference, and were therefore more likely to have AGR than those who were included. A model based on easily available clinical and laboratory variables, including FPG, high-density lipoprotein cholesterol, age and the logarithm of glycated haemoglobin A1c, misclassified 44% of the patients, of whom 18% were overdiagnosed and 26% were underdiagnosed. Conclusion: An OGTT is still the most appropriate method for the clinical assessment of glucometabolic status in patients with coronary heart disease.